1997
DOI: 10.1007/bf00053031
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate tolerance, rebound, and their clinical relevance in stable angina pectoris, unstable angina, and heart failure

Abstract: Vascular tolerance develops rapidly in isolated vascular strips exposed to millimolar concentrations of nitroglycerin. Several mechanisms, including depletion of sulfhydryl groups, reduced biotransformation of nitrates to NO or nitrosothiols, oxygen free radical injury, and downregulation of a membrane-bound enzyme or a nitrate receptor, have been proposed, but the exact mechanism responsible for in-vitro tolerance remains unknown. In-vivo tolerance of the beneficial effects of nitrates on hemodynamics, myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 59 publications
0
50
0
Order By: Relevance
“…At the time, we hypothesised that the greater effects among intermittent compared to daily users may be due to tachyphylaxis associated with daily nitrate use. Tachyphylaxis is commonly observed when treating patients with coronary heart disease with nitrates [20] and similar effects have been observed in ovariectomised rats in which the beneficial effects of nitrates on bone mass decrease with increasing frequency of application [21].…”
Section: Discussionmentioning
confidence: 79%
“…At the time, we hypothesised that the greater effects among intermittent compared to daily users may be due to tachyphylaxis associated with daily nitrate use. Tachyphylaxis is commonly observed when treating patients with coronary heart disease with nitrates [20] and similar effects have been observed in ovariectomised rats in which the beneficial effects of nitrates on bone mass decrease with increasing frequency of application [21].…”
Section: Discussionmentioning
confidence: 79%
“…41 -44 In addition, an increase in angina at rest has been observed during nitrate-free periods with transdermal nitrate formulations, as has a decrease in exercise duration prior to retreatment (often referred to as time-zero effect). 41,42 However, neither an increase in nocturnal angina nor the time-zero effect have been observed with orally administered long-acting nitrates. 40 The exact mechanism underlying the development of tolerance is not fully understood.…”
Section: Nitrate Tolerance and Rebound Anginamentioning
confidence: 99%
“…On a chronic basis, isosorbide dinitrate-hydralazine improved survival in patients with Class 2–3 heart failure [1]. Although the development of tolerance could limit the long-term efficacy of the drug when used on a chronic basis [38], tolerance may be minimized by an appropriate dosing regimen such as the once-daily sustained release formulation used in this study, or with appropriate concomitant therapy such as hydralazine [39, 40]or angiotensin-converting enzyme inhibitor [36, 41]. The present study showed that isosorbide mononitrate in addition to captopril was well tolerated and improved treadmill exercise time in certain patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%